In Vivo Editing of Macrophages through Systemic Delivery of CRISPR‐Cas9‐Ribonucleoprotein‐Nanoparticle Nanoassemblies. Issue 10 (15th August 2019) - Lee, Yi‐Wei; Mout, Rubul; Luther, David C.; Liu, Yuanchang; Castellanos‐García, Laura; Burnside, Amy S.; Ray, Moumita; Tonga, Gulen Yeşilbag; Hardie, Joseph; Nagaraj, Harini; Das, Riddha; Phillips, Erin L.; et al.
Abstract: Macrophages are key effectors of host defense and metabolism, making them promising targets for transient genetic therapy. Gene editing through the delivery of Cas9‐ribonucleoprotein (RNP) provides multiple advantages over gene delivery–based strategies for introducing CRISPR machinery to the cell. There are, however, significant physiological, cellular, and intracellular barriers to the effective delivery of the Cas9 protein and guide RNA (sgRNA) that have to date, restricted in vivo Cas9 protein–based approaches to local/topical delivery applications. Described herein is a new nanoassembled platform featuring coengineered nanoparticles and Cas9 protein that has been developed to provide efficient Cas9‐sgRNA delivery and concomitant CRISPR editing through systemic tail‐vein injection into mice, achieving >8% gene editing efficiency in macrophages of the liver and spleen. Abstract : CRISPR Cas9 ribonucleoprotein (RNP) delivery provides multiple advantages over gene delivery–based strategies. However, cellular barriers to nuclear delivery of Cas9 RNP restrict in vivo Cas9 protein–based approaches to systemic delivery applications. The nanoassemblies provide efficient CRISPR editing through systemic tail‐vein injection into mice, achieving >8% gene editing efficiency in macrophages of the liver and spleen.